Representing O. J.: murder, criminal justice, and mass culture - Barak, Gregg (Harrow and Heston, Publishers, 1996)
This book takes a broad-gauged cultural studies approach to understanding the "trial of the century." A ground-breaking work on the cultural study of newsreporting, entertainment, and the administration of criminal justice. This book defines the field in the emerging area of newsmaking criminology.